EMOTIONAL EFECTS OF COLOURS ON LIFE - Sharma, Ekta (International Journal of Research -GRANTHAALAYAH, 2014)
Color psychology is the study of colors as a determinant of human behavior. Color play a vital role in our in our mood swings. Every color has a unique effects on individuals and stimulates various responses. Take a minute & imagine the world around you without colors, how boring and unexciting life would be. We are influenced by color in every aspect of our life. Kenneth Fehrman ,co-author of the bok COLOR ; says that "Most people are unaware of the profound effect color has on the behavior.".